Dual-Doped Nickel Sulfide for Electro-Upgrading Polyethylene Terephthalate into Valuable Chemicals and Hydrogen Fuel - Chen, Zhijie; Zheng, Renji; Bao, Teng; Ma, Tianyi; Wei, Wei; Shen, Yansong; Ni, Bing‑Jie (Nano-Micro Letters, 2023)
Electro-upcycling of plastic waste into value-added chemicals/fuels is an attractive and sustainable way for plastic waste management. Recently, electrocatalytically converting polyethylene terephthalate (PET) into formate and hydrogen has aroused great interest, while developing low-cost catalysts with high efficiency and selectivity for the central ethylene glycol (PET monomer) oxidation reaction (EGOR) remains a challenge. Herein, a high-performance nickel sulfide catalyst for plastic waste electro-upcycling is designed by a cobalt and chloride co-doping strategy. Benefiting from the interconnected ultrathin nanosheet architecture, dual dopants induced up-shifting d band centre and facilitated in situ structural reconstruction, the Co and Cl co-doped Ni3S2 (Co, Cl-NiS) outperforms the single-doped and undoped analogues for EGOR. The self-evolved sulfide@oxyhydroxide heterostructure catalyzes EG-to-formate conversion with high Faradic efficiency (> 92%) and selectivity (> 91%) at high current densities (> 400 mA cm−2). Besides producing formate, the bifunctional Co, Cl-NiS-assisted PET hydrolysate electrolyzer can achieve a high hydrogen production rate of 50.26 mmol h−1 in 2 M KOH, at 1.7 V. This study not only demonstrates a dual-doping strategy to engineer cost-effective bifunctional catalysts for electrochemical conversion processes, but also provides a green and sustainable way for plastic waste upcycling and simultaneous energy-saving hydrogen production. Highlights: 1 Co and Cl co-doped NiS is an efficient bifunctional electrocatalyst for converting plastic waste into formate and hydrogen with high efficiency and selectivity 2 Dopants regulate the electronic property and accelerate structural reconstruction of NiS for the core ethylene glycol (PET monomer) oxidation reaction 3 PET hydrolysate electrolysis can produce hydrogen gas at an average rate of 50.26 mmol h−1 at 1.7 V